Flexibility and skills: integrating an organizational perspective (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The contemporary practice of human resources, delimited by those requirements of flexibility and adaptation to change, seems to aim at an approach of competencies whose main objective is the identification and management of those be haviours directly related to a good job performance. Therefore, the study of labour competencies will allow us to accede to a level of analysis more broaden of the person realityunder the requirements of flexibility.
Keywords: competencies; flexibility; human resource management.